PENGARUH PEMUPUKAN DAN KEDALAMAN GAMBUT PADA PRODUKSI INOKULUM MIKORIZA ARBUSKULA DALAM PENANGKARAN DENGAN INANG Sorghum bicolor (L.) Moench - Nurtati, Uray; Ekamawanti, Hanna Artuti; Ekyastuti, Wiwik (Universitas Tanjungpura, 2019)
The research was to obtain information about the combination of fertilizers in the production of arbuscular mycorrhizal inoculums of various depths. This research is using an experimental method. The research uses divided plot design (RPT) with a basic RAK pattern. The treatment factor consists of the main plot (peat depth 0-50 cm and 50-100 cm) and subplot is a combination of fertilizer (P1 = without fertilizing; P2 = NPK+rubberwood vinegar; P3 = NPK+peat vinegar; P4 = NPK+fern-root vinegar). Spore breeding process is Â± 3 months. Hosts use sorghum with sterile sand media. The observation variable consisted of the percentage of root infections and the number of spores. Data analysis using ANOVA. Identification of spores based on morphology and Melzer reaction. The results showed that fertilization factors affected the number of spores. The number of spores without fertilization was higher, namely 1642,500 spores compared to combination fertilizers (NPK+fern-root vinegar was 707,667 spores; NPK+rubberwood vinegar was 606,833 spores; NPK+peat vinegar was 206,667 spores). The rate of 0-50 cm colonization without fertilization, NPK+peat vinegar, NPK+rubberwood vinegar is included in the high category. Then in the treatment at 50-100 cm without fertilizing, NPK+peat vinegar, NPK+fern-root vinegar infection rates are also high. The type of spore found is Glomus sp.1; Glomus sp.2; Glomus sp.3; Glomus sp.4. The results of the number of spores and the percentage of root infections showed that organic vinegar was known to not stimulate FMA sporulation, but organic vinegar did not inhibit FMA colonization.Keyword: Mycorrhizal, organic vinegar, peat depth, sorghum